The absence of the brand logo in private label brands: mineral water without logo, non-figurative logo or symbolic logo - David Badajoz; Gemma Freixa (Grafica: Documents de Disseny Gràfic, 2018)
Private label brands have been growing slowly across different countries and have made their place on the shelves and the sales. We ask what would happen to a product without a logo. We explore also if this logo  for a private label product, what would happen if it had a non-symbolic shape rather than a specific figurative new shape, but different from the retail brand.